IKKε-mediated tumorigenesis requires K63-linked polyubiquitination by a cIAP1/cIAP2/TRAF2 E3 ubiquitin ligase complex - Zhou, Alicia Y. (2013)
IκB kinase ε (IKKε, IKBKE) is a key regulator of innate immunity and a breast cancer oncogene, amplified in ~30% of breast cancers, that promotes malignant transformation through NF-κB activation. Here we show that IKKε is modified and regulated by K63-linked polyubiquitination at Lysine 30 and Lysine 401. TNFα and IL-1β stimulation induces IKKε K63-linked polyubiquitination over baseline levels in both macrophages and breast cancer cell lines, and this modification is essential for IKKε kinase activity, IKKε-mediated NF-κB activation and IKKε-induced malignant transformation. Disruption of K63-linked ubiquitination of IKKε does not affect its overall structure but impairs the recruitment of canonical NF-κB proteins. A cIAP1/cIAP2/TRAF2 E3 ligase complex binds to and ubiquitinates IKKε. Together, these observations demonstrate that K63-linked polyubiquitination regulates IKKε activity in both inflammatory and oncogenic contexts and suggests an alterative approach to target this breast cancer oncogene.